Preparation method of quick-freeze-drying low-cost calcium silicate aerogel

By using cheap inorganic calcium salts and inorganic silicone sources, combined with freeze-drying and heat treatment technology, calcium silicate aerogels with three-dimensional nanopore structures were prepared, which solved the high preparation cost and industrialization problems in the prior art, and achieved the Low-cost and efficient preparation of calcium silicate aerogel.

CN119430206APending Publication Date: 2025-02-14NANJING TECH UNIV +1
View PDF 0 Cites 2 Cited by

Patent Information

Application Number
CN202411638863.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-18
Publication Date
2025-02-14

AI Technical Summary

Technical Problem

The existing silicon-based aerogel preparation technology is costly, and the drying process requires high temperature and high pressure, resulting in high industrialization costs and it is difficult to meet the needs of low-cost and efficient preparation.

Method used

Using cheap inorganic calcium salts and inorganic silicon sources as raw materials, calcium silicate aerogels with three-dimensional nanopore structures are prepared by forming calcium silicon hydrolysate, introducing coagulant accelerator, gel and freeze, freeze drying and heat treatment. .

Benefits of technology

It realizes the low-cost and efficient preparation of calcium silicate aerogel, with excellent heat insulation and fire resistance, lowers the technical threshold, and is suitable for large-scale production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119430206A_ABST
    Figure CN119430206A_ABST
Patent Text Reader

Abstract

The invention provides a preparation method of a quick-freeze-drying low-cost calcium silicate aerogel, which takes cheap inorganic calcium salt and inorganic silicon source as raw materials, and provides a preparation method of the calcium silicate aerogel, which comprises the following steps: forming calcium-silicon hydrolysate, introducing a coagulant, gelling and freezing, freeze-drying, carrying out heat treatment and the like, thereby obtaining the quick-freeze-drying low-cost calcium silicate aerogel. The calcium silicate aerogel material with three-dimensional nanopores, low density, temperature resistance, fire prevention and excellent thermal stability is prepared. The temperature-resistant and fireproof calcium silicate aerogel is prepared by taking low-cost inorganic calcium and an inorganic silicon source as raw material parts through quick freeze drying, and has important significance on industrial cost reduction and efficiency improvement.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of preparation of micro-nano materials, and relates to a method for preparing a fast freeze-dried low-cost calcium silicate aerogel with nanostructure, high porosity and high-temperature fire resistance. Background Art

[0002] At present, heat-resistant and fire-proof materials play a vital role in many fields, such as aviation, construction, and electronic manufacturing. Aerogel is a material composed of nanoscale skeletons and pores, with ultra-low density, high porosity, extremely low thermal conductivity and refractive index. This makes aerogel an excellent thermal insulation and high-temperature resistant material, widely used in various high-tech fields. In particular, silicon-based aerogels, due to their abundant silicon sources, relatively simple preparation processes and processes, good controllability, and their transparency is also one of their remarkable characteristics, therefore occupy an important position in practical applications. In addition, alumina aerogels, titanium oxide aerogels, zirconium oxide aerogels, carbon aerogels, carbide aerogels, and composite aerogels prepared in different combinations have also received much attention. However, there are few reports on the preparation and application of calcium silicate composite aerogel materials.

[0003] The average price of tetraethyl orthosilicate (TEOS), a commonly used organic silicon source in commercial silicon-based aerogel heat-resistant insulation materials, is about 15,000 yuan / ton, which directly leads to the high production cost of SiO2 aerogel. In addition, in the drying process of the gel, the supercritical drying method is expensive and needs to be carried out under high temperature and high pressure, and the output is low, and the industrialization cost is high. In order to solve the problems of cost and efficiency, the development of a preparation technology that is both low-cost and efficient is of great significance for promoting the application of new calcium silicate aerogels in the heat-resistant and fireproof materials market. In addition, this method should also be able to ensure the stability and fire resistance of the resulting product under high temperature conditions to meet the strict requirements of industrial applications. Summary of the invention

[0004] The purpose of the present invention is to improve the deficiencies of the prior art and provide a method for preparing a fast freeze-dried low-cost calcium silicate aerogel.

[0005] The present invention uses cheap inorganic calcium salt and inorganic silicon source as raw materials, provides a method for preparing calcium silicate aerogel, and prepares calcium silicate aerogel material with three-dimensional nanopores, low density, heat resistance and fire resistance, and excellent thermal stability by forming calcium silicon hydrolyzate, introducing coagulant, gel and freezing, freeze drying and heat treatment. Using low-cost inorganic calcium and inorganic silicon source as raw materials, partially through rapid freeze drying, heat-resistant and fire-resistant calcium silicate aerogel is of great significance for industrial cost reduction and efficiency improvement.

[0006] The specific technical scheme of the present invention is a method for preparing a low-cost calcium silicate aerogel by rapid freeze drying. By regulating the preparation means, a calcium-silicon composite aerogel with a nanoporous structure is prepared, which has low density, heat resistance, fire resistance, and excellent thermal stability. The specific steps are as follows:

[0007] (1) adding deionized water and an inorganic silicon source into a container, stirring to obtain a transparent solution; then adding an acid catalyst into the transparent solution to adjust the pH value to acidic, and continuing to stir to obtain SiO2 sol; then weighing a calcium inorganic salt and adding it into the SiO2 sol, stirring until completely dissolved, to obtain a calcium silicate sol;

[0008] (2) dropping a coagulant into the calcium silica sol obtained in step (1), stirring, and allowing the sol to stand to allow a gelation reaction to occur; then placing the obtained wet gel into a prepared hydrophobic modifier solution for solvent modification;

[0009] (3) subjecting the wet gel obtained after the solvent modification in step (2) to freezing pretreatment, and drying after the pretreatment to obtain a calcium silicate aerogel precursor;

[0010] (4) The obtained calcium silicate aerogel precursor is placed in a muffle furnace, heated and calcined at a constant temperature to obtain calcium silicate aerogel.

[0011] Preferably, the inorganic silicon source in step (1) is sodium silicate, potassium silicate or alkaline silica sol; sodium silicate and potassium silicate are analytical grade solid drugs; the calcium inorganic salt is calcium chloride dihydrate or anhydrous calcium chloride; and a transparent solution is obtained after stirring for 10 to 15 minutes.

[0012] Preferably, the molar ratio of water, inorganic silicon source and calcium salt in step (1) is (45-90):(0.5-3):1.

[0013] Preferably, the acid catalyst in step (1) is one of hydrochloric acid, acetic acid, propionic acid or oxalic acid; and the pH value is adjusted to 4-5.

[0014] Preferably, the coagulant described in step (2) is 1,2-propylene oxide or epichlorohydrin; the molar ratio of the coagulant to the calcium salt is (6-10):1; and stirring is performed for 5-10 minutes after adding the coagulant.

[0015] Preferably, the hydrophobic modifier solution described in step (2) is a uniform mixture of an organic solvent and a hydrophobic modifier in a volume ratio of (5 to 20):1; the hydrophobic modifier is one of n-octyltriethoxysilane, trimethylchlorosilane, hexamethyldisilazane or dodecyltrimethoxysilane; the organic solvent is one of anhydrous ethanol or tert-butyl alcohol; the modification time is 12 to 24 hours, and the modification temperature is 50 to 60°C.

[0016] Preferably, the freezing pretreatment in step (3) is rapid freezing treatment by liquid nitrogen; the drying method is vacuum freeze drying, and the drying temperature is -60 to -50°C.

[0017] Preferably, the calcination treatment in step (4) is carried out in an oxygen or air atmosphere, with a heating rate of 2 to 5°C / min; the constant temperature calcination temperature is 400 to 700°C, and the constant temperature calcination time is 1 to 2 hours.

[0018] Beneficial effects:

[0019] (1) The present invention significantly reduces the cost of raw materials by using an economical inorganic silicon source. Using water glass as a silicon source is not only low in cost, but also significantly improves the economic benefits of the preparation process.

[0020] (2) The rapid freeze drying technology used in the present invention replaces the supercritical drying technology with high energy consumption, further reducing energy consumption in the production process. This drying technology simplifies equipment requirements, reduces operating costs, and reduces environmental impact. It achieves a significant reduction in costs and meets the high standards of environmental protection in current industrial production, providing a greener and more sustainable preparation solution.

[0021] (2) The low-cost, high-temperature, fire-resistant calcium silicate aerogel prepared by the present invention has excellent three-dimensional nanoporous structure and ultra-low density, so it has excellent thermal insulation and fire-resistant properties. Since its preparation process is simplified, the technical threshold is lowered, making large-scale production possible, thereby significantly reducing the market sales price, making this high-performance material more suitable for industrial applications that require a large amount of fireproof and heat-insulating materials. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] Figure 1 This is a picture of the calcium silicate aerogel sample prepared in Example 1;

[0023] Figure 2 The nitrogen adsorption-desorption curve and pore size distribution diagram of the calcium silicate aerogel in Example 1;

[0024] Figure 3 This is the microstructure diagram of the calcium silicate aerogel in Example 1. DETAILED DESCRIPTION

[0025] The present invention is further described below with reference to examples, but the protection scope is not limited thereto.

[0026] Example 1

[0027] Add 20.27ml (1.125mol) of deionized water to a beaker, measure 7.1g (0.025mol) of solid sodium silicate and pour it into the beaker containing deionized water, stir for 15min to obtain a transparent solution. While continuing to stir, add acetic acid to the transparent solution, adjust its pH value to 5, and continue stirring to obtain SiO2 sol. Weigh 3.68g (0.025mol) of calcium chloride dihydrate (the molar ratio of water, inorganic silicon source and calcium salt is 45:1:1), transfer it to the SiO2 sol, and stir until it is completely dissolved to obtain calcium silica sol. Add 12.24ml (0.175mol) of propylene oxide (the molar ratio of propylene oxide to calcium salt is 7:1) dropwise to the obtained calcium silica sol, stir well for 5min and let it stand to gel. The obtained wet gel is placed in the prepared hydrophobic modifier solution (the hydrophobic modifier solution is anhydrous ethanol and trimethylchlorosilane uniformly mixed in a volume ratio of 10:1), and the solvent is modified at 50°C for 24 hours. The wet gel obtained after solvent modification is placed in liquid nitrogen for freezing treatment. After the freezing pretreatment, vacuum freeze drying (freeze drying temperature is -60°C) is carried out to obtain a calcium silicate aerogel precursor. The obtained solid sample is placed in a muffle furnace, heated from room temperature to 500°C at a heating rate of 5°C / min, and calcined at a constant temperature for 2 hours to finally obtain a calcium silicate aerogel.

[0028] In this embodiment, calcium silicate aerogel samples are prepared as follows Figure 1 As shown, the density is 0.0789g / cm 3 . Figure 2 The calcium silicate aerogel thermal insulation material prepared by the method has a wide range of pore size distribution and a multi-level pore structure, which also ensures its low density and high temperature resistance. Figure 3 This is the microstructure diagram of calcium silicate aerogel, which shows that it has a good pore structure.

[0029] Example 2

[0030] Add 27.02ml (1.5mol) of deionized water to a beaker, measure 3.55g (0.0125mol) of solid potassium silicate and pour it into the beaker containing deionized water, stir for 10min to obtain a transparent solution. While continuing to stir, add propionic acid to the transparent solution, adjust its pH value to 4.5, and continue to stir to obtain SiO2 sol. Weigh 3.68g (0.025mol) of calcium chloride dihydrate (the molar ratio of water, inorganic silicon source and calcium salt is 60:0.5:1), transfer it to the SiO2 sol, and stir until it is completely dissolved to obtain calcium silica sol. Add 10.49ml (0.15mol) of propylene oxide dropwise to the obtained calcium silica sol (the molar ratio of propylene oxide to calcium salt is 6:1), stir well for 10min, and let it stand to gel. The obtained wet gel was placed in the prepared hydrophobic modifier solution (the hydrophobic modifier solution is anhydrous ethanol and hexamethyldisilazane uniformly mixed in a volume ratio of 20:1), and the solvent was modified at 55°C for 20 hours. The wet gel obtained after solvent modification was placed in liquid nitrogen for freezing treatment. After the freezing pretreatment, vacuum freeze drying (freeze drying temperature is -50°C) was carried out to obtain a calcium silicate aerogel precursor. The obtained solid sample was placed in a muffle furnace, heated from room temperature to 450°C at a heating rate of 2°C / min, and calcined at a constant temperature for 2 hours to finally obtain a calcium silicate aerogel.

[0031] The density of the calcium silicate aerogel material prepared in this embodiment is 0.0732 g / cm 3 , and still has a good pore structure after heat treatment at 450℃.

[0032] Example 3

[0033] Add 33.78ml (1.875mol) of deionized water to a beaker, measure 14.21g (0.05mol) of alkaline silica sol and pour it into the beaker containing deionized water, stir for 12min to obtain a transparent solution. While continuing to stir, add hydrochloric acid to the transparent solution, adjust its pH value to 5, and continue to stir to obtain SiO2 sol. Weigh 3.68g (0.025mol) of anhydrous calcium chloride (the molar ratio of water, inorganic silicon source and calcium salt is 75:2:1), transfer it to the SiO2 sol, and stir until completely dissolved to obtain calcium silica sol. Add 13.99ml (0.2mol) of propylene oxide (the molar ratio of propylene oxide to calcium salt is 8:1) dropwise to the obtained calcium silica sol, stir thoroughly for 8min and let it stand to gel. The obtained wet gel was placed in the prepared hydrophobic modifier solution (the hydrophobic modifier solution is a uniform mixture of tert-butyl alcohol and dodecyltrimethoxysilane in a volume ratio of 20:1), and the solvent was modified at 60°C for 12 hours. The wet gel obtained after solvent modification was placed in liquid nitrogen for freezing treatment. After the freezing pretreatment, vacuum freeze drying (freeze drying temperature is -55°C) was carried out to obtain a calcium silicate aerogel precursor. The obtained solid sample was placed in a muffle furnace, heated from room temperature to 600°C at a heating rate of 4°C / min, and calcined at a constant temperature for 1 hour to finally obtain a calcium silicate aerogel.

[0034] The density of the calcium silicate aerogel material prepared in this embodiment is 0.0815 g / cm 3 , and still has a good pore structure after heat treatment at 600℃.

[0035] Example 4

[0036] Add 40.53ml (2.25mol) of deionized water to a beaker, measure 21.32g (0.075mol) of solid sodium silicate and pour it into the beaker containing deionized water, stir for 15min to obtain a transparent solution. While continuing to stir, add oxalic acid to the transparent solution, adjust its pH value to 4, and continue stirring to obtain SiO2 sol. Weigh 3.68g (0.025mol) of calcium chloride dihydrate (the molar ratio of water, inorganic silicon source and calcium salt is 90:3:1), transfer it to the SiO2 sol, and stir until completely dissolved to obtain calcium silica sol. Add 17.49ml (0.25mol) of propylene oxide (the molar ratio of propylene oxide to calcium salt is 10:1) dropwise to the obtained calcium silica sol, stir well for 5min and let it stand to gel. The obtained wet gel was placed in the prepared hydrophobic modifier solution (the hydrophobic modifier solution is a uniform mixture of tert-butyl alcohol and n-octyltriethoxysilane in a volume ratio of 10:1), and the solvent was modified at 55°C for 16 hours. The wet gel obtained after solvent replacement modification was placed in liquid nitrogen for freezing treatment. After the freezing pretreatment, vacuum freeze drying (freeze drying temperature is -50°C) was carried out to obtain a calcium silicate aerogel precursor. The obtained solid sample was placed in a muffle furnace, heated from room temperature to 550°C at a heating rate of 5°C / min, and calcined at a constant temperature for 1.5 hours to finally obtain a calcium silicate aerogel.

[0037] The density of the calcium silicate aerogel material prepared in this embodiment is 0.0.0804 g / cm 3 , and still has a good pore structure after heat treatment at 550℃.

Claims

1. A method for preparing low-cost calcium silicate aerogel by rapid freeze drying, the specific steps of which are as follows: (1) adding deionized water and an inorganic silicon source into a container, stirring to obtain a transparent solution; then adding an acid catalyst into the transparent solution to adjust the pH value to acidic, and continuing to stir to obtain SiO2 sol; then weighing a calcium inorganic salt and adding it into the SiO2 sol, stirring until completely dissolved, to obtain a calcium silicate sol; (2) dropping a coagulant into the calcium silica sol obtained in step (1), stirring, and allowing the sol to stand to allow a gelation reaction to occur; then placing the obtained wet gel into a prepared hydrophobic modifier solution for solvent modification; (3) subjecting the wet gel obtained after the solvent modification in step (2) to freezing pretreatment, and drying after the pretreatment to obtain a calcium silicate aerogel precursor; (4) The obtained calcium silicate aerogel precursor is placed in a furnace, heated and calcined at a constant temperature to obtain calcium silicate aerogel.

2. The preparation method according to claim 1, characterized in that The inorganic silicon source described in step (1) is sodium silicate, potassium silicate or alkaline silica sol; the calcium inorganic salt is calcium chloride dihydrate or anhydrous calcium chloride; and a transparent solution is obtained after stirring for 10 to 15 minutes.

3. The preparation method according to claim 1, characterized in that In step (1), the molar ratio of water, inorganic silicon source and calcium salt is (45-90):(0.5-3):

1.

4. The preparation method according to claim 1, characterized in that The acid catalyst described in step (1) is one of hydrochloric acid, acetic acid, propionic acid or oxalic acid; and the pH value is adjusted to 4-5.

5. The preparation method according to claim 1, characterized in that The coagulant described in step (2) is 1,2-propylene oxide or epichlorohydrin; the molar ratio of the coagulant to the calcium salt is (6-10):1; and stirring is performed for 5-10 minutes after adding the coagulant.

6. The preparation method according to claim 1, characterized in that The hydrophobic modifier solution described in step (2) is a uniform mixture of an organic solvent and a hydrophobic modifier in a volume ratio of (5 to 20):1; the hydrophobic modifier is one of n-octyltriethoxysilane, trimethylchlorosilane, hexamethyldisilazane or dodecyltrimethoxysilane; the organic solvent is one of anhydrous ethanol or tert-butyl alcohol; the modification time is 12 to 24 hours, and the modification temperature is 50 to 60°C.

7. The preparation method according to claim 1, characterized in that The freezing pretreatment described in step (3) is freezing treatment by liquid nitrogen; the drying method is vacuum freeze drying, and the drying temperature is -60 to -50°C.

8. The preparation method according to claim 1, characterized in that In step (4), the heating rate is 2 to 5°C / min; the constant temperature calcination temperature is 400 to 700°C, and the constant temperature calcination time is 1 to 2 hours.

Citation Information

Cited By

  • Low-cost preparation method of silicon-calcium-based aerogel material and product prepared by same

    CN121372220A

  • A low cost method for the preparation of a silica calcium based aerogel material and the product prepared thereby

    CN121372220B